Gardu dalam ‘Struktur’ Politik di Indonesia: Sebentuk Pertemuan Historisisme, Strukturalisme Levi-Strauss dan Posmodernisme (?) - Asti Kurniawati (SASDAYA: Gadjah Mada Journal of Humanities, 2018)
This article aims to examine the possibility of meeting three paradigms of Historicism, Structuralism of Levi-Strauss and Postmodernism by analyzing the book of Abidin Kusno, Penjaga Memory; Gardu di Perkotaan Jawa, using the paradigm of Levi-Strauss structuralism, exploring the paradigm that used by the author and the philosophy behind the writing history. This step was done to find out the possible paradigm meeting between those used by the author of the book and the Levi-Strauss structuralism paradigm that used to analyze the book.